Impact of the COVID-19 Pandemic on Immunomodulatory and Immunosuppressive Therapies in Dermatology: Patient and Physician Attitudes in Argentina (2020)
We performed a cross-sectional study using 2 questionnaires. The first questionnaire, which was aimed at patients with inflammatory skin disease susceptible to immunomodulating/immunosuppressant treatment (psoriasis [Ps], atopic dermatitis [AD], hidradenitis suppurativa [HS], and others), consisted of 5 questions on age, dermatologic disease, current treatment, sources of information regarding COVID-19, and preventive measures. The questionnaire was sent to 1500 patients of the Civil Association for Psoriasis Patients (AEPSO). The second questionnaire, which was aimed at dermatologists, consisted of 12 questions on communication routes and patient care, sources of information, and behavior regarding treatments. The questionnaire was sent to 350 dermatologists of the Argentinian Psoriasis Society (SOARPSO) and the Argentinian Dermatology Society (SAD). Both questionnaires were sent via WhatsApp or email on 19 March 2020. Responses were accepted up to March 27, 2020. Qualitative variables were expressed as absolute numbers and percentages. The STATA (StataCorp, version 14.2) statistical software package was used to perform the statistical analysis. The study complied with the ethical principles of the Helsinki declaration.